Longitudinal tunnel ventilation control. Part 2: Non-linear observation and disturbance rejection. (June 2017) - Fuhrmann, Martin; Euler-Rolle, Nikolaus; Killian, Michaela; Reinwald, Markus; Jakubek, Stefan
Abstract: Tunnel ventilation control plays a key role in tunnel fire safety, nevertheless there is considerable scope for improving conventional control schemes. This paper proposes a practical approach on how to improve the disturbance attenuation ability of longitudinal tunnel ventilation systems by adding a non-linear unknown disturbance observer to an existing two-degrees-of-freedom control scheme in order to establish active disturbance rejection. The focus of attention is on tunnels using jet fans for fresh air supply. Conventional control does not specifically take into account external disturbances that tunnels are exposed to due to the momentum introduced by moving vehicles and meteorological circumstances like wind load onto the portals, or meteorological pressure differences between the portals. The proposed control scheme provides promising simulation as well as experimental results of a real tunnel implementation. The observer and rejection scheme's convergence and stability is analysed based on Lyapunov theory. Abstract : Highlights: An existing feedforward control is enhanced by an efficient disturbance rejection. A non-linear unknown input observer is developed. Active disturbance rejection is enabled. Observer stability is analysed based on Lyapunov theory. Results of the successful observer implementation are shown.